Determinan Keputusan Petani Tembakau dalam Mengadopsi Good Agricultural Practices - Muwahhid, Suryani Latifah; Suwarto, Suwarto; Widiyanto, Widiyanto (Jurnal Sosial Ekonomi Pertanian, 2024)
The development of the tobacco commodity that still relies on traditional cultivation methods without technological innovation threatens productivity and quality. Therefore, improving cultivation methods through adopting Good Agricultural Practices (GAP) is essential to address this issue. The adoption of GAP in Colomadu District remains relatively low. This study analyzes the factors influencing tobacco farmers' decisions to adopt GAP in Colomadu District, Karanganyar Regency. This study uses a quantitative method with a survey technique. The research location was purposively determined in Colomadu District, Karanganyar Regency. The sample consisted of 30 heads of families, selected using simple random sampling. Logistic regression analysis using IBM SPSS 29 was conducted to analyze the data. The results showed that 67% of the respondent farmers (20 heads of families) did not adopt GAP, while the remaining 33% (10 heads of families) had adopted GAP. The study also found that the nature of innovation partially significantly influenced tobacco farmers' decisions to adopt GAP, whereas communication channels, social systems and promotional efforts by agricultural extension workers had no significant partial effect on tobacco farmers' decisions to adopt GAP.